2008
DOI: 10.1007/s00380-008-1044-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness in pre-and postmenopausal women with suspected coronary artery disease

Abstract: Carotid intima-media thickness (CIMT) is an early marker of coronary artery disease (CAD). This study aimed to evaluate CIMT value for CAD prediction in pre-and postmenopausal women referred for coronary angiography with angina-like symptoms and a positive result of the treadmill test. The study comprised 321 women referred for coronary angiography with symptoms suggesting CAD. Carotid intima-media thickness was measured in common, bifurcation, and internal carotid artery, and expressed as the mean maximum val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…The atherosclerotic risk of postmenopausal women is 3.4 times higher compared with premenopausal women [17], and IMT has been shown to be a valid predictor of cardiovascular events in these patients [18]. Surprisingly, the median IMT of our sample was within the normal range for women of equal age [19].…”
Section: Discussioncontrasting
confidence: 55%
“…The atherosclerotic risk of postmenopausal women is 3.4 times higher compared with premenopausal women [17], and IMT has been shown to be a valid predictor of cardiovascular events in these patients [18]. Surprisingly, the median IMT of our sample was within the normal range for women of equal age [19].…”
Section: Discussioncontrasting
confidence: 55%
“…A widely used non-invasive measure to evaluate subclinical atherosclerosis is carotid intima-media thickness (cIMT) [44]. An increased cIMT value is a predictor of coronary artery disease in both pre-and postmenopausal women [45]. Two recent meta-analyses showed that cIMT values are higher in women after preeclampsia compared with those in women experiencing a normotensive pregnancy, both at time of pregnancy and in the first 10 years postpartum [46,47].…”
Section: Signs Of Subclinical Atherosclerosis After Preeclampsiamentioning
confidence: 99%
“…The gradual damage induces atherosclerosis, reduces the diameter of blood vessels, and then causes vascular stenosis 13 . Kablak and his colleagues reported that carotid intima-media thickness (CIMT) is a strong CAD predictor in both pre- and postmenopausal women, in contrast to that in the menopausal women 14 . While the association of menopause with CIMT and stroke has been suggested in the studies mentioned above, it is still unclear whether different menopause stages can affect CIMT differentially, thereby leading to potential differences in development and stability of carotid plaques in Chinese women population.…”
Section: Introductionmentioning
confidence: 99%